2013
DOI: 10.2147/dmso.s51325
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension and obesity in patients with type 2 diabetes mellitus in observational studies: a systematic literature review

Abstract: BackgroundHypertension and obesity are known to contribute, directly or indirectly, to the development of long-term complications of type 2 diabetes mellitus (T2DM). Knowing the prevalence of these comorbidities is important for determining the size of the population that may benefit from strategies that reduce blood pressure and weight while controlling blood glucose.MethodsIn this systematic literature review, electronic searches of PubMed, Embase, and the Cochrane Library were conducted to identify observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
217
3
14

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(248 citation statements)
references
References 87 publications
14
217
3
14
Order By: Relevance
“…The same was shown in Nigeria [12], although the Nigerian study showed a higher rate of hypertension (60.9%). In Europe and Asia the prevalence of hypertension in diabetics was shown to be above 70% [13], which is also higher compared to what we found. The literature shows that high rates of microvascular complications in diabetics can be attributed to frequent high blood pressure [5].…”
Section: Resultscontrasting
confidence: 81%
“…The same was shown in Nigeria [12], although the Nigerian study showed a higher rate of hypertension (60.9%). In Europe and Asia the prevalence of hypertension in diabetics was shown to be above 70% [13], which is also higher compared to what we found. The literature shows that high rates of microvascular complications in diabetics can be attributed to frequent high blood pressure [5].…”
Section: Resultscontrasting
confidence: 81%
“…Reports from Western countries show that the prevalence of obesity among diabetes patients has increased since the 1980s [17,18]. A review of diabetes patients showed that the prevalence of obesity, defined as BMI ≥30 kg/m 2 or waist circumference ≥102 cm in men and ≥88 cm in women, was 50.9-98.6% in Europe and 56.1% in Asia [2]. The percentage of Japanese patients with BMI ≥25 kg/m 2 was reported to be 33.9% in 2004 [19], which is similar to the findings from 2006 in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 Diabetes Mellitus (T2DM) and hypertension (HT) are common chronic disorders that often coexist [1]. Large epidemiological studies showed that the coexistence of elevated Blood Pressure (BP) in patients with T2DM is associated with increased risk of mortality and morbidity because of cardiovascular complications [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%